ð˜šð˜°ð˜³ð˜¨ð˜©ð˜¶ð˜® ð˜´ð˜¶ð˜¥ð˜¢ð˜¯ð˜¦ð˜¯ð˜´ð˜¦ AS COVER CROP AND BIOLOGICAL PRODUCTS ON INCIDENCE OF ð˜šð˜¤ð˜ð˜¦ð˜³ð˜°ð˜µð˜ªð˜¯ð˜ªð˜¢ ð˜´ð˜¤ð˜ð˜¦ð˜³ð˜°ð˜µð˜ªð˜°ð˜³ð˜¶ð˜® AND YIELD OF TOBACCO - Luis de Menezes, Edson; Ferraz-Almeida, Risely (REVISTA DE AGRICULTURA, 2021)
Brazil is the world's second largest producer of tobacco (Nicotiana tabacum) with part of its production concentrated in Santa Catarina. The incidence of Sclerotinia sclerotiorum in tobacco areas has promoted a decrease in productivity, and control alternatives are needed due to the limited use of agrochemicals for the crop. With the hypothesis that the sudan grass (Sorghum sudanense) and Trichoderma harzianum reduce the attack of S. sclerotiorum in tobacco crops on the coast of Santa Catarina; the objective here was to test the incidence of S. sclerotiorum and the use of sudan grass associated with biological products on tobacco yield. A study with application of straw from sudan grass (SG); SG + Trichoderma harzianum (TH); SG + TH + Melaleuca alternifolia essential oil; SG + TH + Bacillus subtilis & Bacillus licheniforimis; and SG + TH + Bacillus subtilis in a conventional system of tobacco were carried out in São João do Sul and Santa Rosa do Sul, Santa Catarina. Results showed that in São João do Sul, there was no difference between the treatments in yield and incidence of S. sclerotiorum. However, in Santa Rosa do Sul, the association of SG + TH, SG + TH + B. subtilis & B. licheniforimis, and SG + TH + B. subtilis presented greater yields than others. In both sites, sudan grass and associations promoted a higher financial return compared to control. More studies are requested to elucidate the physiological effect of biological products and sudan grass as a cover crop on tobacco.